THE ANALYSIS OF STUDENTS’ ABILITY IN WRITING SHORT STORIES - Ikin Syamsudin Adeani (JALL (Journal of Applied Linguistics and Literacy), 2020)
This researchis aimed to determine the students’ ability of Indonesian Education Study Program,Faculty of Teacher Training and Education, Galuh Ciamis University, in writing short stories. The students are still lack of studying the literary of short story, instead they tend to read the popular short stories. The method used in this research is descriptive method. The results of this study are as follows. First, to obtain the clear illustrationwhether the students are able to write literature short stories or popular short stories. Second, to position their short stories in the development of Indonesian short stories, especially among students. Keywords: analysis, writing short story, literary short stories, popular short stories